Robert Ludlum's the ares decision : a covert-one novel - Mills, Kyle; Ludlum, Robert (New York : Grand Central Publishing, 2012)
With U.S. intelligence agencies wracked by internal power struggles and paralyzed by bureaucracy, the President was forced to establish his own clandestine group-- Covert-One. It is only activated as a last resort, when the threat is on a global scale and time is running out.
Keywords: Microbiology -- Fiction; Thrillers (Fiction)